Effects of structured inquiry-based teaching on thinking skills of biology students - Lee, Tze Jiun (2018)
Inquiry-based teaching is said to have positive outcomes on students’ performances especially for science students in the development of Science, Technology, Engineering and Mathematics (STEM). However, teachers seem to have some difficulties implementing inquiry teaching during class. These challenges include how to have effective discussions to promote inquiry teaching, how to implement an inquiry teaching and cover all the subject’s content at the same time, how to manage an inquiry classroom effectively, and how to measure the effectiveness of the inquiry. Therefore, this study aims to suggest elements to better understand the effect of structured inquiry-based teaching on the thinking skills of biology students. These elements include the duration of teaching, planning and preparation, cooperative learning and hands-on practices. In addition, the present study investigated students’ curiosity levels which act as an extraneous variable that needed to be controlled before the treatment begins. A quantitative quasi-experimental (pre-,post-test) was conducted in Kuala Lumpur, Malaysia for 8 weeks. Two intact classes were taken from Form 4 Biology students. The study was to compare structured inquiry-based teaching (S-IBT) and traditional teaching (Con-T) on the effectiveness of Biology students’ thinking skills, knowledge retention and learning gain among the students. A total of 64 responses were analysed using the SPSS software. Univariate statistical analyses were employed to inspect and explain the data in this study. There were no significant differences between the two groups for their pre-test and also curiosity level. After the treatments, the post-test was administrated, followed by a knowledge retention test after 3 weeks. Learning gain ratio was measured by using pre-test and post-test thinking skills test scores. The findings showed that S-IBT students performed better than Con-T students in their post-test on thinking skills and knowledge retention. The effect size using eta squared shows a range from .18 to .74, indicating large effects. The medium amount of learning gain ratio leaves much room for improvement in future studies. Structured inquiry-based teaching can be seen as an effective teaching method in enhancing students’ performances especially in thinking skills. Overall, these four elements can be a guideline for whoever that wishes to apply structured inquiry-based teaching.